2009
DOI: 10.1890/08-1626.1
|View full text |Cite
|
Sign up to set email alerts
|

Water availability directly determines per capita consumption at two trophic levels

Abstract: Abstract. Community ecology has long focused on energy and nutrients as currencies of species interactions. Evidence from physiological ecology and recent studies suggest that in terrestrial systems, water may influence animal behavior and global patterns of species richness. Despite these observations, water has received little attention as a currency directly influencing animal species interactions. Here, we show that the per capita interaction strength between predatory wolf spiders and their primary prey, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 44 publications
3
109
0
Order By: Relevance
“…Specifically, large spiders reduced cricket populations under dry ambient conditions, but had no effect with water supplementation (figure 1, B1 versus B2). This result followed expectations from previous research in cages [15], and thus supports the hypothesis that short-term, small-scale changes in per capita effects can roughly predict longer-term population-level dynamics [19]. Similarly, as predicted, large spiders had positive effects on moist leaf material (reduced herbivory) under dry conditions ( figure 1, B1), but in contrast to predictions (no effect), large spiders increased herbivory where direct free water was added (reverse of a trophic cascade; figure 1, B2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, large spiders reduced cricket populations under dry ambient conditions, but had no effect with water supplementation (figure 1, B1 versus B2). This result followed expectations from previous research in cages [15], and thus supports the hypothesis that short-term, small-scale changes in per capita effects can roughly predict longer-term population-level dynamics [19]. Similarly, as predicted, large spiders had positive effects on moist leaf material (reduced herbivory) under dry conditions ( figure 1, B1), but in contrast to predictions (no effect), large spiders increased herbivory where direct free water was added (reverse of a trophic cascade; figure 1, B2).…”
Section: Discussionsupporting
confidence: 92%
“…Previous work has shown that water balance can influence consumption of moist food for particular consumers [9,15]. We hypothesized that this alteration of consumption would lead to changes in the strength of top-down effects in real food webs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, environmental water conditions, usually categorized as wet or dry, have the potential to impact the consumption habits of riparian consumers [147,148]. Strikingly, the abundance of riparian organisms was greater where surface water and groundwater resources were added, regardless of the presence of a river, an abundant and natural water source [144].…”
Section: The Role Of Water Availability In Shaping Riparian Trophic Smentioning
confidence: 99%
“…Strikingly, the abundance of riparian organisms was greater where surface water and groundwater resources were added, regardless of the presence of a river, an abundant and natural water source [144]. When reviewing the interaction between two trophic levels, researchers found that predatory spiders altered their prey consumption; in dry conditions, crickets consumed more moist leaves than dry litter, and the spiders under the dry conditions consumed significantly more crickets under the same conditions [147]. These preferences indicate that food consumption can vary across multiple levels of the trophic system depending upon water availability [34,147].…”
Section: The Role Of Water Availability In Shaping Riparian Trophic Smentioning
confidence: 99%